2013
DOI: 10.1200/jco.2012.47.2167
|View full text |Cite
|
Sign up to set email alerts
|

German Adjuvant Intergroup Node-Positive Study: A Phase III Trial to Compare Oral Ibandronate Versus Observation in Patients With High-Risk Early Breast Cancer

Abstract: Adjuvant treatment with oral ibandronate did not improve outcome of patients with high-risk early breast cancer who received dose-dense chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(53 citation statements)
references
References 36 publications
4
47
0
2
Order By: Relevance
“…61 With respect to other bisphosphonates, one trial that studied adjuvant oral ibandronate showed no effect on DFS or OS in patients with node-positive, early-stage breast cancer treated with dose-dense chemotherapy. 62 Data on adjuvant oral pamidronate show no benefit on either reducing fractures or recurrence to bone in patients with breast cancer receiving adjuvant chemotherapy. 63 …”
Section: Bisphosphonatesmentioning
confidence: 99%
“…61 With respect to other bisphosphonates, one trial that studied adjuvant oral ibandronate showed no effect on DFS or OS in patients with node-positive, early-stage breast cancer treated with dose-dense chemotherapy. 62 Data on adjuvant oral pamidronate show no benefit on either reducing fractures or recurrence to bone in patients with breast cancer receiving adjuvant chemotherapy. 63 …”
Section: Bisphosphonatesmentioning
confidence: 99%
“…In addition, recent subgroup analysis supports the hypothesis that bisphosphonate mainly works in oestrogen-deprived patients, i.e. patients at least 5 years into menopause or with ovarian function suppression [14,15]. Last but not least, the median followup of this study is too short to fully assess treatment effects in patients with hormone-receptor-positive/ HER2-negative tumours.…”
Section: Discussionmentioning
confidence: 51%
“…Abstract: Breast cancer is characterized by tendency to early metastasizing: about 6 % of patients already have metastatic form of the disease at the time of diagnosis. The most frequent target are bones: for the frequency of bone metastasis, breast cancer is on the second place among malignant tumors and on the first place in absolute incidence [1,2,3,4]. On the early stages, metastatic bone lesions can be asymptomatic.…”
Section: выводыmentioning
confidence: 99%
“…Наиболее частой мишенью при этом являются кости (костная система): по частоте метастазирования в кости РМЖ занимает 2-е место среди злокачественных опухолей, а по удельному весу -1-е [1,2,3,4]. На ранних стадиях метастатическое поражение костей бывает бессимптомным [5,6].…”
unclassified